Analytic Filmmaking: A Response to Critics. Issue 3 (September 2014) - Germano, Roy
<x content-type="archive" xml:space="preserve">Abstract</x> I would like to begin by thanking Jeff Isaac for organizing this symposium. I am also grateful to the five commentators—Henry Farrell, Jeffrey Gould, Davide Panagia, Sunita Parikh, and Dvora Yanow—for taking the time to think about my target essay and to offer such thought provoking comments and critiques. Even if the commentators have reservations about the analytic filmmaking approach, I am encouraged by their enthusiasm for the fundamental idea contained in my target essay: Audiovisual media can and should be used to publish social science research. This rejoinder aims to briefly clarify my positions on some of the major issues raised by the commentators. The first part addresses questions about how we should structure audiovisual publications, while the second part examines the nexus between analytic filmmaking and scientific inquiry.